The lost continent - Goss, Brittany Lynn, author; Becker, Leslee, advisor; Schwartz, Steven, committee member; Alexander, Ruth, committee member (Colorado State University. Libraries, 2013)
This collection of short stories was written and revised between 2010 and 2013 during my tenure as a student in the M.F.A. in Creative Writing program at Colorado State University. Taken as a polished creative portfolio, these works document my development as a young writer and serve as fulfillment of the thesis portion of the M.F.A. degree in Fiction.